A modified method of total RNA isolation and quantitative analysis of superoxide dismutase gene expression from different organs of Ipomoea carnea - Mishra, Panchanand; Sabat, Surendra C. (Acta Biologica Szegediensis, 2013)
Ipomoea carnea (I. carnea) has unique biological features for the study of cellular and molecular adaptation mechanisms due to presence of diverse alkaloid and its cadmium tolerance capacity. The present study was directed to quantify total SOD content in different organs of the plant and further extended to relative quantification of cytosolic CuZn-SOD, Fe-SOD and Mn-SOD mRNA. A modified method of total RNA isolation from the plant I. carnea which is rich in alkaloids has been described. Total SOD content of apical and lateral bud was highest, but transcript abundance of cytosolic CuZn-SOD was much lower as compared to root and leaves. In these cases Mn- and Fe-SOD mRNA was relatively higher and perhaps that was contributing to the high SOD activity. However, less photosynthetically active organs like root and petal show less SOD activity but mRNA level of cytosolic CuZn-SOD was competitive in these cases. The results showed that SODs in different compartments are differently regulated and each SOD isoenzyme must be performing specific function related to its cellular localization and expression of the protein isoforms depend upon local accumulation of superoxide.